Cure-dependent thermomechanical modelling of the stress relaxation behaviour of composite materials during manufacturing. (March 2017) - Brauner, Christian; Frerich, Tim; Herrmann, Axel S
This study contributes to the understanding of the mechanism behind process-induced distortions and stresses related to the Resin Transfer Moulding manufacturing process. The objective is to comprehend the phenomena and to identify related parameters. During the manufacturing process, engineering constants of the matrix are changing and are influenced by the existence of a large number of effects. A viscoelastic material model has been derived. This developed material model integrates a dependency of the time–temperature–polymerisation and fibre volume content on the relaxation behaviour of residual stresses in a transversally isotropic reinforced material. The model is validated using a test case on the coupon level and results / limitations are discussed.